2020
DOI: 10.1038/s41467-020-16390-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcript isoform sequencing reveals widespread promoter-proximal transcriptional termination in Arabidopsis

Abstract: RNA polymerase II (RNAPII) transcription converts the DNA sequence of a single gene into multiple transcript isoforms that may carry alternative functions. Gene isoforms result from variable transcription start sites (TSSs) at the beginning and polyadenylation sites (PASs) at the end of transcripts. How alternative TSSs relate to variable PASs is poorly understood. Here, we identify both ends of RNA molecules in Arabidopsis thaliana by transcription isoform sequencing (TIF-seq) and report four transcript isofo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 74 publications
2
47
0
Order By: Relevance
“…Interestingly, further analysis indicated that these SUMO binding sites were predominantly located around TSSs, including promoter-proximal regions and potential 5′ UTR regions ( Figure 1 C, Supplemental Figure 3 A). Because previous work indicated that these regions are critical for TF binding and transcription regulation ( Ohler and Wassarman, 2010 ; Shao and Zeitlinger, 2017 ; Thomas et al., 2020 ), our results suggest that SUMOylation may play a role in the modulation of gene transcription. By contrast, SUMO signals were weak in intergenic, transposon, and heterochromatin regions ( Supplemental Figure 4 ).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Interestingly, further analysis indicated that these SUMO binding sites were predominantly located around TSSs, including promoter-proximal regions and potential 5′ UTR regions ( Figure 1 C, Supplemental Figure 3 A). Because previous work indicated that these regions are critical for TF binding and transcription regulation ( Ohler and Wassarman, 2010 ; Shao and Zeitlinger, 2017 ; Thomas et al., 2020 ), our results suggest that SUMOylation may play a role in the modulation of gene transcription. By contrast, SUMO signals were weak in intergenic, transposon, and heterochromatin regions ( Supplemental Figure 4 ).…”
Section: Resultsmentioning
confidence: 57%
“…Our ChIP-seq data indicated that SUMO-associated chromatin peaks are predominantly located on promoter-TSS gene regions, which harbor active epigenetic markers ( Figure 1 D and 1F) ( He et al., 2011 ), suggesting that SUMOylation plays a role in transcriptional activation. Interestingly, these SUMO-enriched sites are preferentially localized around the TSS ( Figure 1 C), similar to the distribution of TFs ( Ohler and Wassarman, 2010 ; Shao and Zeitlinger, 2017 ; Thomas et al., 2020 ), such as HSFA1a ( Supplemental Figure 12 A). Consistently, predicted motifs in the HS SUMO peaks are also highly enriched in these regions ( Supplemental Figure 12 B).…”
Section: Discussionmentioning
confidence: 58%
“…2E). Transcription of Arabidopsis genes frequently produces short promoter-proximal RNAs (sppRNA) which are sensitive to the HEN2 exonuclease and terminate about 100 nt downstream from the TSS [31]. We found that 5’ borders of genes called by TranscriptomeReconstructoR are in a better agreement with the sppRNA termination sites than 5’ borders of their annotated mates in both TAIR10 and Araport11 (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…A representative example of such gene on Fig. S4 (see Additional File 2) demonstrates that its split nature can be further supported by independent TIF-seq dataset which detects both ends of mature RNA transcripts [31].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, evidence of transcriptional stalling via RNAPII backtracking triggering nucleolytic degradation of the nascent RNA indicates that TTSa-RNAs may be implied in the termination of mRNA transcription ( Valen et al, 2011 ). For instance, a recent study in A. thaliana indicated that promoter-proximal RNAPII stalling can regulate plant gene transcription ( Thomas et al, 2020 ). Thus, it is reasonable to infer that mammalian TTSa-RNAs might participate in the regulation of gene transcription through the modulation of transcriptional termination ( Figure 3 ).…”
Section: Functions Of Tanrsmentioning
confidence: 99%